Divorce Due to Wife Nusyuz (Analysis of Decision Number 286/Pdt.G/2022/Pa.Brb) - Muhammad Muhyiddin (Sharia Journal and Education Center Publishing, 2023)
Abstract This research is motivated by the decision of the Judge at the Barabai Religious Court class I B, where one of the rulings of the decision punishes the Petitioner to pay mut'ah to the Respondent in the amount of Rp. 3,200,000.00 (three million two hundred thousand rupiah) and the Respondent is categorized by the Judge who decides the case into the category of nusyuz. The Respondent was categorized into the category of nusyuz by the Judge because she did not want to serve the inner needs of the Petitioner on the grounds that she was sleepy and tired.The purpose of this research is to find out the basis of the judge's consideration in deciding the amount of mut'ah value and to find out what legal problems arise in decision number 286/Pdt.G/2022/Pa.Brb. This research uses normative legal research methods and uses a statute approach and case approach. As for analyzing this research, the author uses a qualitative method. By first collecting the necessary legal materials from document studies, then grouped according to the problem and the legal materials are interpreted and analyzed in order to obtain clarity or solution of a problem sought.The results of this study the author found: First, the judge in deciding, especially punishing the Petitioner in paying mut'ah to the Respondent, uses the method of jurimetry and the principle of appropriateness, which conceptually the use of the jurimetry formula is not appropriate, it is necessary to look again at how the wife's devotion and the length of time the husband and wife live in a joint residence. Second, other legal problems that arise in the decision, namely related to the nusyuz of a wife, because refusing an invitation to bed is not necessarily punished as nusyuz. Then, in the application of the Principle of Decency itself, it should pay more attention to the devotion or behavior of each party to the other. Keywords: Divorce, Nusyuz, Court Decision. Abstrak Penelitian ini dilatarbelakangi oleh putusan Hakim Pengadilan Agama Barabai kelas I B, dimana salah satu amar putusannya menghukum Pemohon untuk membayar mut'ah kepada Termohon sebesar Rp. 3.200.000,00 (tiga juta dua ratus ribu rupiah) dan Termohon dikategorikan oleh Hakim yang memutus perkara tersebut ke dalam kategori nusyuz. Termohon dikategorikan ke dalam kategori nusyuz oleh Hakim karena tidak mau melayani kebutuhan batin Pemohon dengan alasan mengantuk dan capek. Tujuan dari penelitian ini adalah untuk mengetahui dasar pertimbangan hakim dalam memutuskan besaran nilai mut'ah dan untuk mengetahui problematika hukum apa saja yang muncul dalam putusan nomor 286/Pdt.G/2022/Pa.Brb. Penelitian ini menggunakan metode penelitian hukum normatif dan menggunakan pendekatan perundang-undangan (statute approach) dan pendekatan kasus (case approach). Adapun dalam menganalisis penelitian ini, penulis menggunakan metode kualitatif. Dengan terlebih dahulu mengumpulkan bahan-bahan hukum yang diperlukan dari studi dokumen, kemudian dikelompokkan sesuai dengan permasalahan dan bahan-bahan hukum tersebut diinterpretasikan dan dianalisis guna memperoleh kejelasan atau pemecahan dari suatu permasalahan yang dicari Hasil penelitian ini penulis menemukan: Pertama, hakim dalam memutus khususnya menghukum Pemohon dalam membayar mut'ah kepada Termohon menggunakan metode yurimetri dan asas kepatutan, yang mana secara konseptual penggunaan rumus yurimetri tersebut kurang tepat, perlu dilihat lagi bagaimana pengabdian istri dan lamanya suami istri tinggal dalam satu tempat tinggal bersama. Kedua, permasalahan hukum lain yang muncul dalam putusan tersebut, yaitu terkait dengan nusyuznya seorang istri, karena menolak ajakan tidur tidak serta merta dihukumi nusyuz. Kemudian, dalam penerapan Asas Kepatutan itu sendiri, seharusnya lebih memperhatikan pengabdian atau perilaku masing-masing pihak terhadap pihak lainnya. Kata Kunci: Perceraian, Nusyuz, Putusan Pengadilan.